Nepticulidae (Lepidoptera) of East Asia (2). Study of a collection sample deposited at the Russian Academy of Sciences, with descriptions of new species and a checklist - Rocienė, Agnė; Stonis, Jonas R. (Zootaxa, 2013)
Over the few couple of decades, the Nepticulidae of East Asia have been the subject of continuing investigation. Male genitalia of the nepticulid species described from Primorskiy Kray (the Russian Far East) were re-examined in the preced-ing paper in this journal. The present paper continues our study on the diversity and systematics of the Nepticulidae of East Asia based on a sample of specimens collected in 1974–1990 at various sites of the southern part of Primorskiy Kray and treats 35 species: two new taxa (Ectoedemia ortiva sp. nov. and E. species 219) and 33 other species. Seventeen of them are briefly discussed and illustrated with photographs of male genitalia. Two new synonyms are proposed, and three new distribution records are provided. We also provide an updated checklist of the Nepticulidae of East Asia, which com-prises 105 species; 67 species occur in the Russian Far East and 53 in Japan (20 of which occur both in Japan and Russia). Species with Euro-East Asiatic distribution currently comprise 11% of the Japanese fauna and 16% of the continental fau-na of the Russian Far East, Primorskiy Kray.